2021
DOI: 10.1002/jmri.27993
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Analysis of Pharmacokinetic Heterogeneity Within Tumor Based on the Unsupervised Decomposition of Dynamic Contrast‐Enhanced MRI for Predicting Histological Characteristics of Breast Cancer

Abstract: Background Breast tumor heterogeneity is associated with histological characteristics. However, pharmacokinetic (PK) heterogeneity within tumor might merit further exploration. Purpose To enhance the predictive power of molecular subtypes, Ki‐67, and tumor grade by analyzing PK heterogeneity within tumor based on dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI). Study Type Retrospective. Population Two hundred and eight biopsy‐proven breast cancer patients, randomly divided into a training cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Physiological and mechanical properties of tumor have been shown to characterize heterogeneity in gene expression, and phenotype for Glioblastoma (GBM) 47,53,55,64,71,[125][126][127][128][129][130][131] . Many studies [31][32][33][34][35][36][37][38][39][40][41][42][132][133][134][135][136][137] Zhang et al 41,137 have recently shown the association between the subregional PK-based radiomics information of breast tumor and its histological characteristics. They have also shown that compared to the entire tumor region, subregional PK-based radiomics information can enhance the predictive performance of the radiomic models 41,137 .…”
Section: Subfigures 4b-f and 4h-l Clearly Demonstrate How Different T...mentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological and mechanical properties of tumor have been shown to characterize heterogeneity in gene expression, and phenotype for Glioblastoma (GBM) 47,53,55,64,71,[125][126][127][128][129][130][131] . Many studies [31][32][33][34][35][36][37][38][39][40][41][42][132][133][134][135][136][137] Zhang et al 41,137 have recently shown the association between the subregional PK-based radiomics information of breast tumor and its histological characteristics. They have also shown that compared to the entire tumor region, subregional PK-based radiomics information can enhance the predictive performance of the radiomic models 41,137 .…”
Section: Subfigures 4b-f and 4h-l Clearly Demonstrate How Different T...mentioning
confidence: 99%
“…Many studies [31][32][33][34][35][36][37][38][39][40][41][42][132][133][134][135][136][137] Zhang et al 41,137 have recently shown the association between the subregional PK-based radiomics information of breast tumor and its histological characteristics. They have also shown that compared to the entire tumor region, subregional PK-based radiomics information can enhance the predictive performance of the radiomic models 41,137 . This highlights the importance of the inclusion of local information in characterization of tumor heterogeneity and strongly supports the dynamic convolutional radiomics analysis used in this study.…”
Section: Subfigures 4b-f and 4h-l Clearly Demonstrate How Different T...mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), and pharmacokinetic (PK) modeling, in particular, can identify tumor subregions that have distinct patterns of contrast uptake 9 and can reveal tissue perfusion and permeability. 10 In clinical practice, a hypervascular area typically shows a high volume transfer constant (K trans ) value indicative of increased tumor perfusion, even though K trans is defined as a volume transfer constant from tumor capillaries to the extravascular extracellular space (EES). 11,12 It has been shown in preclinical studies that areas near the tumor rim show high K trans values, whereas those near the core show low K trans values.…”
mentioning
confidence: 99%
“…In this issue of JMRI, Zhang et al 7 employed a radiomic pipeline to evaluate the predictive ability of pharmacokinetic parameters for breast cancer molecular subtypes, Ki‐67 expression level, and tumor grade. Specifically, they compared the volume transfer constant K trans features from tumor subregions, obtained by a CAM decomposition method, to those of the entire tumor, and found enhanced predictive performance with the habitat imaging approach.…”
mentioning
confidence: 99%